Prevalence and genotyping of Echinococcus granulosus sensu lato from livestock in north-eastern Kenya - Omondi, H.A.; Gitau, G.; Gathura, P.; Mulinge, E.; Zeyhle, E.; Kimeli, P.; Bett, Bernard K. (Cambridge University Press, 2020)
Cystic echinococcosis (CE) is a zoonotic disease of cosmopolitan distribution and caused by the larval stage of the dog tapeworm, Echinococcus granulosus sensu lato (s.l.). CE occurs in the wider African continent and in Kenya, notably in the Maasailand and Turkana regions; however, recent studies demonstrate its presence in other parts of Kenya. This study determined the occurrence of CE in livestock (camels, goats, sheep and cattle) in Isiolo, Garissa and Wajir counties, and characterized the species of E. granulosus s.l. present. An abattoir survey was used to determine the presence of CE in various organs in livestock. Polymerase chain reaction-restriction fragment length polymorphism and sequencing of the mitochondrial NADH dehydrogenase subunit 1 gene was used for genotyping. A total of 1368 carcasses from 687 goats, 234 camels, 329 sheep and 118 cattle were inspected for the presence of hydatid cysts. The overall proportion of infections was 29.1% in camels, 14.4% in cattle, 9.9% in goats and 8.2% in sheep. The liver was the most infected organ, while only the lung of camels harboured fertile cysts. Of the 139 cysts genotyped, 111 (79.9%) belonged to Echinococcus canadensis (G6/7) and 20 (14.4%) to E. granulosus sensu stricto. One and two cysts were identified as Taenia saginata and unknown Taenia species, respectively. There was a significant association between county of origin and species of the animal with occurrence of CE. This study reports, for the first time, the characterization of Echinococcus species in livestock from Garissa and Wajir counties, and the current situation in Isiolo county. The fertility of cysts in camels and frequency of E. canadensis (G6/7) in all livestock species indicate that camels play an important role in the maintenance of CE in the north-eastern counties of Kenya.